ALEKSANDER KRAWCZUK’S READINGS OF LITERATURE - Szargot, Barbara (Prace Polonistyczne, 2022)
The aim of the article is to reflect on the works of the historian of antiquity Aleksander Krawczuk. In particular, it focuses on the relationships among historiography, literature, the history of literature, and literary criticism in the works of the author of Poczet cesarzy rzymskich. In her analyses, the author refers to the way in which the category of truth operates in contemporary historical discourse and to the role of the narrative in historiography. For this purpose, in the first part of her article, she lists different scholarly approaches to this matter. In the second part, Szargot examines Krawczuk’s perspectives on the past, as presented in two of his works: Spotkania z Petroniuszem and Polska za Nerona.